Bali Membangun kembali Industri Pariwisata: 1950-an - Adrian Vickers (Jurnal Kajian Bali (Journal of Bali Studies), 2013)
AbstractThe period of nation-building following Indonesia’sindependence is still little documented. The creationof Bali’s tourist industry during the colonial period isbetter documented that the re-creation of the industry inthe post-War period. This period is important because itwas Balinese who became the main agents of the rebornindustry. The industry was built on three main pillars, theprovision of accommodation, the creation of souvenirsthrough the “Artshops”, and the creation of itineraries.Building on the remnants of the colonial period, Balineseresponded to interactions with a number of key Westernfigures, using them as guides to Western tastes and needs.Although the strategy of “Cultural Tourism” is usuallyascribed to the Suharto era, it was a product of Balineseagency in the period between 1950 and 1971.